On display Instagram, the self, and the city - Boy, John D.; Uitermark, Justus 1978- (Oxford University Press, 2024)
"Two billion people around the world use Instagram. On Display examines how a platform that is unfailingly polished and ruthlessly judgmental shapes us and our environments. Instagram has a reputation for shallowness, but the ongoing self-presentation it demands confronts users with profound dilemmas as it compels them to do serious soul-searching. What do we want to show of ourselves? Who are we? What do we want to be? On Display is a book about how people remake their worlds through social media. It examines how personalities, relations, social movements, urban subcultures, and city streets change as they are represented on Instagram. Through computational analysis, the authors reveal how Instagram is implicated in social inequalities, while interviews and ethnographic vignettes provide an intimate account of the desires and anxieties that animate the platform. Whereas many have argued that social media promote polarization, On Display shows that this is not so for Instagram: its users are embedded in large and diverse networks, compelling them to take many, often contradictory expectations into account. Existing theories about social media are often a poor fit for Instagram. The authors propose a new perspective: social media are stages for status displays rather than public spheres for the exchange of arguments"--
Keywords: Beeinflussung; Social Media; Instagram; Instagram (Electronic resource); Online social networks / Psychological aspects; Photographs / Psychological aspects; Social status; Self; Cities and towns in mass media; Social media and society; Réseaux sociaux (Internet) / Aspect psychologique; Statut social; Moi (Psychologie); Villes dans les médias; Médias sociaux et société; social status